Effectiveness of Physical Education Program on the Domains of the University Students, Attitudes toward Physical Fitness - Kadum, Fadhel; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: To determine the effectiveness of physical education program on the domains of the universitystudents attitudes of physical activity and health, physical activity and mental health, physical activity and nutritiontoward physical fitness.Methodology: A quasi-experimental design is carried out throughout the present study with the application oftest-retest approach through the period from February 3rd 2013 to June 30th 2013. The study is conducted onpurposive sample of(40) Undergraduate Students at the College of Science University of Baghdad . The sample isConsisted of (20) males and (20) females. Questionnaire of two main parts, Personal and demographicinformation and students' attitudes about physical activity is constructed and employed.Result: In general, the results show a significant positive improvement in students' attitudes toward physicalfitness after implementation of the education program.Recommendation: The physical education program should be presented to wide-range number of universitystudents with different fields of interest.